The Effect of Zinc Oxide Supported on Gelatin Mesoporous Silica (GSBA-15) on Structural Character and Their Methylene Blue Photodegradation Performance - Maria Ulfa; Ida Setiarini (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Gelatin mesoporous silica SBA-15 (GSBA-15) with rod-like morphology has been successfully synthesized by hydrothermal method using P-123:gelatin, then aged at 90 °C for 24 h and calcined at 550 °C for 5 h. GSBA-15 was impregnated with ZnO amounts of 1; 5; and 10 wt% to obtain Zn/GSBA-15. Samples were characterized by X-ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), Scanning Electron Microscopy (SEM), and Brunauer-Emmett-Teller (BET). The efficiency of methylene blue photodegradation was determined by a UV-Vis spectrophotometer. The FTIR result is functional groups of ZnO/GSBA-15, those were Si−O−Si, −OH, Zn−OH, and Zn−O. The morphology of ZnO/GSBA-15 was rod-like, and it consisted of silica, oxygen, and Zn. The surface area and pore volume of GSBA-15 declined (surface area from 520.8 to 351.9 m2/g and pore volume from 0.707 to 0.564 cm3/g) after ZnO impregnation due to pore blocking. At the same time, increasing pore diameter (from 2.82 nm to 3.19 nm) and crystallite size (from 5.1 nm to 12.6 nm) were observed due to the overlapping of ZnO-Silica particles. The increasing incorporation of ZnO on the silica GSBA-15 framework increases the photodegradation performance from 88.76% to 94.90% due to the high surface area, functional group rich, and dispersion of ZnO active sites. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).